The Effectiveness of the Make a Match Method in Improving the Learning Outcomes of Islamic Religious Education in Elementary Schools - Supa'at Supa'at (FITK UIN Walisongo Semarang, 2025)
This research aims to improve the learning outcomes of grade II students of SD Negeri 2 Kendengsidialit on the material